Универсальный электромагнитно совместимый с сетью преобразователь для электроприводов - Дрючин, Виктор Гаврилович; Самчелеев, Юрий Павлович; Морозов, Дмитрий Иванович; Андреева, Наталья Ивановна; Скурятин, Юрий Васильевич (НТУ "ХПИ", 2010)
In article is offered universal electromagnetic compatible converter with network of the constant voltage, which can work in mode of the source of the current, voltages or powers. The converter has an uncontrolled rectifier, but ensuring the mode and electromagnetic compatibility is provided by power active filter under corresponding to control.
Universal electromagnetic compatible converter with network for electric drive
Keywords: фильтр силовой; фильтр активный; источник мощности; устройство вычислительное; нагрузка